PHONOLOGICAL THEORIES AND THEIR PRIMITIVES OF ANALYSIS (Muitas Vozes, 2021)
In this text, the primitives of analysis in the sound domain or phonic component of three remarkable theories in the history of Linguistics are discussed and made explicit: the Structuralist Phonology (SAUSSURE, 2012) and the concept of phoneme as a segment of the speech sound chain that has a distinctive unit functionality; the Generative Phonology (CHOMSKY; HALLE, 1968) and the concept of distinctive features as minimal binary properties (acoustic or articulatory) that simultaneously compose speech sounds; and, finally, in the scope of Laboratory Phonology, the Gestural Phonology (BROWMAN; GOLDSTEIN, 1992) and the concept of articulatory gesture, an analysis unit that includes categorical and variable perception, addressing the speech gradience. After presenting the three selected theories and their primitives of analysis, the possible approach of each theory in the phonetic and phonology interface is then mentioned.